THE INFLUENCE OF INQUIRY BASED COLLABORATIVE INNOVATIVE LEADERSHIP ON LEARNING COMMUNITIES WITH THE MODERATING ROLE OF ORGANIZATIONAL CULTURE - Wulandari, Herlina Tri; Susanto, Heri; Darsinah, Darsinah; Rohmah, Wafrotur (Jurnal As-Salam, 2025)
This study analyzes the effect of inquiry-based, collaborative, and innovative leadership on the development of productive learning communities in vocational high schools (SMKs), with organizational culture as a moderating variable. Inquiry-based, collaborative, innovative leadership is a leadership style that encourages teachers to jointly formulate critical questions, reflect on teaching practices, and systematically test new solutions. This approach is expected to strengthen reflective and collaborative practices within teacher learning communities, which often remain formal and administrative. Organizational culture is positioned as a set of school-level values, norms, and routines that can either enhance or hinder collaboration and collective learning. Using a quantitative explanatory approach, the study employed Structural Equation Modeling (SEM) with AMOS 26.0. The sample included 360 productive subject teachers selected through proportionate stratified random sampling from five state vocational high schools in Central Java. The results show that inquiry-based collaboration and organizational culture both have positive and significant effects on productive learning communities. Moreover, their interaction demonstrates a highly significant effect, indicating that an open, collaborative, and learning-oriented organizational culture strengthens the influence of inquiry-based, collaborative, and innovative leadership on teachers' collective learning.